A new approach to limit fault current with series-parallel resonance strategy - Arikan, Oktay; Kucukaydin, Baris (SPRINGER, 2020)
Increased power generation depending on demand, becoming widespread of distributed generation systems connecting to the grid in parallel, and the expansion of network cause the fault current levels to increase in power systems. Fault current limiters are being developed to prevent damages triggered by high fault currents and indirect effects on the network. In this study, a new series-parallel resonance-type fault current limiter (SPRFCL) is proposed. In normal operation, the SPRFCL that remains passively in the system in series resonance at the main frequency limits the fault current by means of the high impedance shown by parallel resonance when a fault condition is detected with the control circuit. The most important advantages of the SPRFCL are that in all short-circuit fault types, limiting the fault currents with a low amplitude oscillation, restraining the rising rate of fault current and also the sags in PCC (common coupling point) voltage can be successfully suppressed. SPRFCL is mathematically modeled, and simulation studies are performed in PSCAD. The performance of SPRFCL on critical parameters is revealed by presenting the obtained results.
Keywords: Fault current limiter; Series-parallel resonance; Voltage sag; Power quality; NETWORK; Engineering